Arabic Learning Management at Islamic Boarding Schools in Lampung - Amirudin, Amirudin; Basyar, Syarifudin; Akmansyah, Muhammad; Subandi, Subandi; Shahril, Sulthan (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
This study was focused on exploring the management of Arabic learning at Islamic boarding schools that have different characters, namely Usuluddin, al-Hikmah, and Nurul Huda Islamic Islamic boarding schools in terms of planning, implementing, and evaluating the learning. This research was descriptive qualitative research where the researchers acted as the main instrument of the research. the data was also obtained from other sources, namely the religious teachers, students, scholars, and documents. The data was collected through data collecting techniques in the form of interviews, observation, and documentation. The results showed that there were differences emphasis on the Arabic learning management objectives in the three Islamic boarding schools. The Usuluddin Islamic boarding school emphasized listening and speaking skills where various programs were facilitated to enable the students to speak fluently and listen to routine speeches, Arabic debates, muhawarah, and yaumu al-lugah. At the Al-Hikmah and Nurul Huda Islamic boarding schools, the Arabic learning management emphasized the reading and writing skills as well as translating turas books. It is recommended for the Arabic learning management to focus on four aspects of language proficiency so that the students can be proficient in the comprehensive language (active and passive).